Witnessing the Truth as the Basis of All Pedagogical Activity - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 2005)
All pedagogical activity that is rooted in the depths of human striving to get to know the world, has acquired a wide scope. It is important, for this reason, to identify the fundamental sources that will guarantee the success in the practices of education. One of those possible sources can be traced back to the paradigm of truth that in essence relates to educational practices and is revealed in pedagogical activity through the following channels: a) the truth about the surrounding world that yields to exploration - and in the ideal case, this kind of truth involves the components of our empirical experience, science and religious faith and facilitates the shaping of the subject-based teacher - student relationships; b) the truth about man – this kind of truth outlines the instances and possibilities of man to get to know the world, it also speaks about the development and subordination of those possibilities; e) the synthesis of truth about man and the world that is based on the pedagogue's effort to witness the truth and that cables the personality-focused attitude towards students. However, in the majority of cases, present-day pedagogues tend to limit their educational activity to conveying the truth about the surrounding world only and often ground their professional activity on the merely subject-based type of relationships with students.
Keywords: educational activity; scientific and religious faith truth; witnessing the truth